Calle Próspero 1913 - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1913)
SPANISH: Jiron Prospero in 1913, you can see carriage and track without asphalt.
ENGLISH: Jirón Próspero en el año 1913, se puede ver carruaje y pista sin asfalto

SPANISH: Jiron Prospero in 1913, you can see carriage and track without asphalt.
ENGLISH: Jirón Próspero en el año 1913, se puede ver carruaje y pista sin asfalto
Prospero Street in 1913
Keywords: S/N